Novel Trifluoromethyl Pyrimidinone Compounds With Activity Against Mycobacterium tuberculosis - Hembre, Erik; Early, Julie V.; Odingo, Joshua; Shelton, Catherine; Anoshchenko, Olena; Guzman, Junitta; Flint, Lindsay; Dennison, Devon; McNeil, Matthew B.; Korkegian, Aaron; Ovechkina, Yulia; Ornstein, Paul; et al. (Frontiers in Chemistry, 2021)
The identification and development of anti-tubercular agents has been an increasing priority. We identified the trifluoromethyl pyridiminone series of compounds in a whole cell screen against Mycobacterium tuberculosis. Fifteen primary hits had minimum inhibitory concentrations (MICs) with good potency (IC90 <5 µM). We conducted a structure activity relationship investigation for this series. We designed and synthesized an additional 44 molecules and tested all analogs for activity against M. tuberculosis and cytotoxicity against the HepG2 cell line. Substitution at the 5-position of the pyrimidinone tolerated a wide range of groups including branched and straight chain alkyl and benzyl groups. Substitution at the 6-position of the pyrimidinone was required for activity, with trifluoromethyl preferred, but phenyl and benzyl were tolerated. A 2-pyridyl group was required for activity; substitution on the 5-position of the pyridyl ring was tolerated but not on the 6-position. Active molecules from the series demonstrated low selectivity, with cytotoxicity being an issue. However, the best molecule had an MIC (IC90) of 4.9 µM with no cytotoxicity (IC50 >100 µM). The series was inactive against Gram negative bacteria but showed good activity against Gram positive bacteria and yeast. A representative molecule from this series showed rapid concentration- dependent bactericidal activity against replicating bacilli with ~4 log kill in <7 days. Overall the biological properties were promising, if cytotoxicity could be reduced. There is scope for further medicinal chemistry optimization to improve in cytotoxicity, without any major change in structural features.